The Biggest Book of Party Games Ever! - Edited by Edwards, Kerrin (London Carlton Books, 2001)
The Biggest Book of Party Games Ever! is packed with over 750 party games, tricks and practical jokes and drinking games of all kinds - from ones that you can play with all the family to those you'll just want to play with your best (!) friends. A series of symbols indicates the kind of game described and there are lists of any equipment needed to play. The games are divided into various categories, beginning with those that will get any party off to a good start and help break the ice, and carrying on with games that require a bit of energy. There are some that require a lot of bottle (of both kinds!), others which need some musical accompaniment, and some which need a little acting ability. In addition there are tricks and practical jokes to impress and humiliate your pals in equal measure. But no matter what the age range of your guests is, there is something for everyone and once you have The Biggest Book of Party Games Ever!, you can be sure your party will go with a swing.
Includes Illustrations.
Keywords: Games